Preparation and application of high-performance asphalt-based porous carbon material
The high-performance pitch-based porous carbon material prepared through steps such as crushing and heat treatment solves the problem of using high-cost raw materials in the existing technology, achieves a significant increase in specific surface area and pore volume, and has a cost-effective preparation method and excellent pores. Structural performance.
Patent Information
- Application Number
- CN202411856238.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-17
AI Technical Summary
In the prior art, when preparing high-performance asphalt-based porous carbon materials, there are high-cost raw materials such as carbon nanotubes and graphene, which leads to inefficient production methods and are difficult to achieve under the premise of ensuring specific surface area and pore volume. .
Through the steps of crushing, heat treatment, pre-oxidation, jet crushing, carbonization, activation, pickling, water washing and drying, high-performance pitch-based porous carbon materials with hierarchical pore structure are prepared, avoiding the use of high-cost raw materials.
It is possible to increase the specific surface area and pore volume of pitch-based porous carbon materials without using high-cost raw materials, so that they can meet the performance requirements of porous carbon raw materials in the vapor deposition silicon carbon process, which has significant economic advantages and higher Pore structure richness.
Smart Images

Figure CN119330354A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemistry and energy materials, and in particular relates to the preparation and application of a high-performance asphalt-based porous carbon material. Background Art
[0002] The negative electrode materials of lithium batteries mainly include carbon-based materials, oxide-based materials, phosphorus-based materials, and silicon-based materials. Among them, the advantage of silicon-based materials is mainly high theoretical specific capacity, and its disadvantage is mainly serious volume expansion during charging and discharging.
[0003] On the other hand, one of the common silicon-based materials is silicon carbon, and the common silicon carbon material mainly refers to vapor-deposited silicon carbon. The core steps of the preparation method of vapor-deposited silicon carbon mainly include: preparation of porous carbon, silane deposition of nano-silicon particles, and carbon layer coating.
[0004] Correspondingly, one of the necessary conditions for vapor-deposited silicon carbon to achieve higher charge and discharge efficiency and better cycle stability is that the above-mentioned porous carbon material must have: a larger specific surface area and a larger pore volume.
[0005] In addition, one of the common raw materials of the above-mentioned porous carbon material is asphalt, and the fundamental purpose of the preparation method of the porous carbon material is to perform sufficient and appropriate pore-making operations on the asphalt.
[0006] For example, a Chinese invention patent application with application publication number CN118206115A and application publication date 2024.06.18 discloses a method for preparing a high-performance asphalt-based porous carbon material, the steps of which include: mixing asphalt and carbon nanotubes to obtain a precursor; pretreating and crushing the obtained precursor; adding graphene and drying; pre-oxidation treatment; carbonization and activation treatment.
[0007] The high-performance asphalt-based porous carbon material in this invention patent application has the following advantages: it has a higher micropore volume and specific surface area, can provide more active sites for chemical vapor deposition of silicon, and improves deposition efficiency.
[0008] However, the above preparation method still has at least the following shortcomings in actual implementation, namely: Its total pore volume is 0.68-0.88cm 3 / g, with a specific surface area of 1320 m 2 / g or more. On this basis, its raw material composition includes carbon nanotubes and graphene, which are relatively expensive, so the preparation method is not economical and efficient enough. Summary of the invention
[0009] The present invention provides a method for preparing a high-performance asphalt-based porous carbon material. The technical problem to be solved is: how to more simply and economically increase the specific surface area and pore volume of the asphalt so that the product meets the performance requirements of the vapor phase deposition silicon carbon process for the porous carbon raw material.
[0010] In addition, the present invention also provides the above material and application of the above material.
[0011] The technical solution adopted by the present invention to solve the above problems is: a method for preparing a high-performance asphalt-based porous carbon material, which comprises the following steps in sequence: S1. Crushing: crushing the asphalt raw material to 200 mesh to obtain crushed material; S2. Heat treatment: heat treating the crushed material under a nitrogen atmosphere until the light component content in the crushed material is 45-72 wt % to obtain a precursor; S3, pre-oxidation: in a high-temperature carbonization furnace, the precursor is oxidized to obtain a pre-oxidized material; S4, air flow crushing: the pre-oxidized material is subjected to air flow crushing operation to crush it to D50=5-8μm to obtain a granular material; S5, carbonization: in a high-temperature carbonization furnace, carbonizing the granular material to obtain a carbonized product; S6, activation: the carbonized product remains in the high-temperature carbonization furnace, and an alkaline activator is added to perform an activation operation to obtain an activated product; S7, acid washing and water washing: the activated product is subjected to several groups of acid washing and water washing operations in sequence to obtain a washing material: S8, drying: performing hot air drying operation on the washed material to obtain the final high-performance asphalt-based porous carbon material.
[0012] In S4 of the present invention, the air flow pulverization operation is used to control the particle size and improve the comprehensive performance of the material.
[0013] Too small a particle size (<5 μm) will result in a low overall compaction density of the subsequently prepared porous carbon material, which will further result in a low compaction density of the prepared silicon-carbon negative electrode material, ultimately reducing the energy density of the silicon-carbon negative electrode material.
[0014] However, a particle size that is too large (>8 μm) will result in the prepared porous carbon material particles being too large, affecting the diffusion of silane gas during chemical vapor deposition and reducing the deposition efficiency. Therefore, the particle size range of D50=5-8 μm was finally determined.
[0015] The light components refer to organic compounds such as wax, oil, and solvent in asphalt, which are light and volatile. The light components have a significant impact on important properties of asphalt, such as viscosity, temperature sensitivity, and oxidizability.
[0016] A further preferred technical solution is that in S2, the heat treatment temperature is 150-550°C and the time is 30-300 min.
[0017] A further preferred technical solution is that in S3, the atmosphere of the oxidation operation is oxygen or air, the oxidation temperature is 150-400° C., and the oxidation time is 2-5 hours.
[0018] A further preferred technical solution is that in S5, the temperature of the carbonization operation is 400-1000°C, the constant temperature carbonization time is 2-4h, and the heating rate from room temperature to the carbonization temperature is 2-7°C / min.
[0019] A further preferred technical solution is that in S6, the alkaline activator is any one of potassium hydroxide and sodium hydroxide or a mixture of the two.
[0020] A further preferred technical solution is that in S6, the weight ratio of the alkaline activator to the carbonized product is (1-4):1, the atmosphere of the activation operation is nitrogen, the activation temperature is 600-1000°C, and the activation time is 1-2h.
[0021] A further preferred technical solution is that: in S7, dilute hydrochloric acid is used for pickling operation, and the combination of pickling and water washing is repeated ≥ 3 times.
[0022] A further preferred technical solution is that in S8, the end point of the hot air drying operation is that the moisture content of the washing material is ≤ 0.03 wt%.
[0023] A high-performance asphalt-based porous carbon material obtained by the preparation method: the high-performance asphalt-based porous carbon material has a hierarchical pore structure, the hierarchical pore structure includes micropores, mesopores and macropores, the pore diameter of the micropores is <2nm, the pore diameter of the mesopores is 2-50nm, and the pore diameter of the macropores is >50nm.
[0024] An application of the high-performance asphalt-based porous carbon material: the high-performance asphalt-based porous carbon material is used to prepare negative electrodes for lithium-ion batteries, sodium-ion batteries and supercapacitors.
[0025] Compared with the prior art, the present invention has at least the following beneficial effects: First, the high-performance asphalt-based porous carbon material does not use relatively high-cost raw materials such as carbon nanotubes and graphene while ensuring sufficient specific surface area and sufficient pore volume values, so that the preparation method has outstanding advantages of simplicity and economy; Second, the specific surface area of this high-performance asphalt-based porous carbon material can reach 2500 m 2 / g or more, the pore volume can reach 1.1cm 3 / g or more, which is significantly higher than the existing common asphalt-based porous carbon materials; Third, the high-performance asphalt-based porous carbon material has a graded pore structure while ensuring a large pore volume value. The graded pore structure includes micropores, mesopores and macropores. The pore size of the micropores is <2nm, the pore size of the mesopores is 2-50nm, and the pore size of the macropores is >50nm. The above-mentioned graded pore structure shows that the porous carbon material has the advantages of rich and comprehensive pore structure, which can ultimately improve the conductive performance of the silicon-carbon negative electrode.
[0026] Fourth, in the above-mentioned hierarchical pore structure, the high-performance asphalt-based porous carbon material also has a relatively higher microporosity, that is, the hierarchical pore structure is mostly micropores, which is more conducive to improving the pore volume parameters of the porous carbon material itself and the corresponding conductivity of the silicon-carbon negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an electron microscope photograph of the final high-performance asphalt-based porous carbon material in Example 1 of the present invention.
[0028] Figure 2 This is an electron microscope photograph of the final high-performance asphalt-based porous carbon material in Example 2 of the present invention.
[0029] Figure 3 This is an electron microscope photograph of the final high-performance asphalt-based porous carbon material in Example 3 of the present invention.
[0030] Figure 4 This is an electron microscope photograph of the final high-performance asphalt-based porous carbon material in Example 4 of the present invention.
[0031] Figure 5 This is an electron microscope photograph of the final high-performance asphalt-based porous carbon material in Example 5 of the present invention. DETAILED DESCRIPTION
[0032] The following descriptions are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention.
[0033] Example 1 like Figure 1 As shown, a method for preparing a high-performance asphalt-based porous carbon material comprises the following steps in sequence: S1. Crushing: crushing the asphalt raw material to 200 mesh to obtain crushed material; S2, heat treatment: heat treating the crushed material under a nitrogen atmosphere until the light component content in the crushed material is 58wt%, to obtain a precursor, wherein the heat treatment temperature is 300°C and the time is 45min; S3, pre-oxidation: in a high-temperature carbonization furnace, the precursor is oxidized to obtain a pre-oxidized material, wherein the oxidation atmosphere is oxygen, the oxidation temperature is 270° C., and the oxidation time is 3.5 h; S4, air flow crushing: performing air flow crushing operation on the pre-oxidized material, crushing it to D50=7μm, and obtaining a granular material; S5, carbonization: in a high-temperature carbonization furnace, the granular material is carbonized to obtain a carbonized product, wherein the carbonization temperature is 600° C., the constant temperature carbonization time is 4 hours, and the heating rate from room temperature to the carbonization temperature is 5° C. / min; S6, activation: the carbonized product is left in a high-temperature carbonization furnace, and an alkaline activator is added to perform an activation operation to obtain an activated product, wherein the alkaline activator is potassium hydroxide, and the weight ratio of potassium hydroxide to the carbonized product is 3:1, the atmosphere of the activation operation is nitrogen, the activation temperature is 850°C, and the activation time is 1.5h; S7, pickling and washing: the activated product is subjected to multiple pickling and washing operations in sequence to obtain a washing material, wherein dilute hydrochloric acid is used for pickling operation and distilled water is used for washing operation; S8. Drying: performing hot air drying operation on the washed material to obtain a final high-performance asphalt-based porous carbon material, wherein the end point of the hot air drying operation is that the moisture content of the washed material is ≤0.03wt%.
[0034] The high-performance asphalt-based porous carbon material has a hierarchical pore structure, which includes micropores, mesopores and macropores. The pore size of the micropores is less than 2nm, the pore size of the mesopores is 2-50nm, and the pore size of the macropores is >50nm.
[0035] The application of this high-performance asphalt-based porous carbon material: used to prepare negative electrodes for lithium-ion batteries, sodium-ion batteries and supercapacitors.
[0036] Example 2 like Figure 2 As shown, a method for preparing a high-performance asphalt-based porous carbon material comprises the following steps in sequence: S1. Crushing: crushing the asphalt raw material to 200 mesh to obtain crushed material; S2. Heat treatment: heat treating the crushed material under a nitrogen atmosphere until the light component content in the crushed material is 46 wt %, to obtain a precursor, wherein the heat treatment temperature is 300° C. and the time is 70 min; S3, pre-oxidation: in a high-temperature carbonization furnace, the precursor is oxidized to obtain a pre-oxidized material, wherein the oxidation atmosphere is air, the oxidation temperature is 270° C., and the oxidation time is 3.5 h; S4, air flow crushing: performing air flow crushing operation on the pre-oxidized material, crushing it to D50=7μm, and obtaining a granular material; S5, carbonization: in a high-temperature carbonization furnace, the granular material is carbonized to obtain a carbonized product, wherein the carbonization temperature is 600° C., the constant temperature carbonization time is 4 hours, and the heating rate from room temperature to the carbonization temperature is 5° C. / min; S6, activation: the carbonized product is left in a high-temperature carbonization furnace, and an alkaline activator is added to perform an activation operation to obtain an activated product, wherein the alkaline activator is potassium hydroxide, and the weight ratio of potassium hydroxide to the carbonized product is 3:1, the atmosphere of the activation operation is nitrogen, the activation temperature is 850°C, and the activation time is 1.5h; S7, acid washing and water washing: the activated product is subjected to acid washing and water washing operations for multiple times in sequence to obtain a washing material, wherein dilute hydrochloric acid is used for the acid washing operation and distilled water is used for the water washing operation: S8. Drying: performing hot air drying operation on the washed material to obtain a final high-performance asphalt-based porous carbon material, wherein the end point of the hot air drying operation is that the moisture content of the washed material is ≤0.03wt%.
[0037] The high-performance asphalt-based porous carbon material has a hierarchical pore structure, which includes micropores, mesopores and macropores. The pore size of the micropores is less than 2nm, the pore size of the mesopores is 2-50nm, and the pore size of the macropores is >50nm.
[0038] The application of this high-performance asphalt-based porous carbon material: used to prepare negative electrodes for lithium-ion batteries, sodium-ion batteries and supercapacitors.
[0039] Example 3 like Figure 3 As shown, a method for preparing a high-performance asphalt-based porous carbon material comprises the following steps in sequence: S1. Crushing: crushing the asphalt raw material to 200 mesh to obtain crushed material; S2, heat treatment: heat treating the crushed material under a nitrogen atmosphere until the light component content in the crushed material is 67wt%, to obtain a precursor, wherein the heat treatment temperature is 300°C and the time is 30min; S3, pre-oxidation: in a high-temperature carbonization furnace, the precursor is oxidized to obtain a pre-oxidized material, wherein the oxidation atmosphere is air, the oxidation temperature is 270° C., and the oxidation time is 3.5 h; S4, air flow crushing: performing air flow crushing operation on the pre-oxidized material, crushing it to D50=7μm, and obtaining a granular material; S5, carbonization: in a high-temperature carbonization furnace, the granular material is carbonized to obtain a carbonized product, wherein the carbonization temperature is 600° C., the constant temperature carbonization time is 4 hours, and the heating rate from room temperature to the carbonization temperature is 5° C. / min; S6, activation: the carbonized product is left in a high-temperature carbonization furnace, and an alkaline activator is added to perform an activation operation to obtain an activated product, wherein the alkaline activator is potassium hydroxide, and the weight ratio of potassium hydroxide to the carbonized product is 3:1, the atmosphere of the activation operation is nitrogen, the activation temperature is 850°C, and the activation time is 1.5h; S7, acid washing and water washing: the activated product is subjected to acid washing and water washing operations for multiple times in sequence to obtain a washing material, wherein dilute hydrochloric acid is used for the acid washing operation and distilled water is used for the water washing operation: S8. Drying: performing hot air drying operation on the washed material to obtain a final high-performance asphalt-based porous carbon material, wherein the end point of the hot air drying operation is that the moisture content of the washed material is ≤0.03wt%.
[0040] The high-performance asphalt-based porous carbon material has a hierarchical pore structure, which includes micropores, mesopores and macropores. The pore size of the micropores is less than 2nm, the pore size of the mesopores is 2-50nm, and the pore size of the macropores is >50nm.
[0041] The application of this high-performance asphalt-based porous carbon material: used to prepare negative electrodes for lithium-ion batteries, sodium-ion batteries and supercapacitors.
[0042] Example 4 like Figure 4 As shown, a method for preparing a high-performance asphalt-based porous carbon material comprises the following steps in sequence: S1. Crushing: crushing the asphalt raw material to 200 mesh to obtain crushed material; S2, heat treatment: heat treating the crushed material under a nitrogen atmosphere until the light component content in the crushed material is 58wt%, to obtain a precursor, wherein the heat treatment temperature is 300°C and the time is 45min; S3, pre-oxidation: in a high-temperature carbonization furnace, the precursor is oxidized to obtain a pre-oxidized material, wherein the oxidation atmosphere is air, the oxidation temperature is 270° C., and the oxidation time is 3.0 h; S4, air flow crushing: performing air flow crushing operation on the pre-oxidized material, crushing it to D50=7μm, and obtaining a granular material; S5, carbonization: in a high-temperature carbonization furnace, the granular material is carbonized to obtain a carbonized product, wherein the carbonization temperature is 900° C., the constant temperature carbonization time is 4 hours, and the heating rate from room temperature to the carbonization temperature is 5° C. / min; S6, activation: the carbonized product is left in a high-temperature carbonization furnace, and an alkaline activator is added to perform an activation operation to obtain an activated product, wherein the alkaline activator is potassium hydroxide, and the weight ratio of potassium hydroxide to the carbonized product is 3:1, the atmosphere of the activation operation is nitrogen, the activation temperature is 850°C, and the activation time is 1.5h; S7, acid washing and water washing: the activated product is subjected to acid washing and water washing operations for multiple times in sequence to obtain a washing material, wherein dilute hydrochloric acid is used for the acid washing operation and distilled water is used for the water washing operation: S8. Drying: performing hot air drying operation on the washed material to obtain a final high-performance asphalt-based porous carbon material, wherein the end point of the hot air drying operation is that the moisture content of the washed material is ≤0.03wt%.
[0043] The high-performance asphalt-based porous carbon material has a hierarchical pore structure, which includes micropores, mesopores and macropores. The pore size of the micropores is less than 2nm, the pore size of the mesopores is 2-50nm, and the pore size of the macropores is >50nm.
[0044] The application of this high-performance asphalt-based porous carbon material: used to prepare negative electrodes for lithium-ion batteries, sodium-ion batteries and supercapacitors.
[0045] Example 5 like Figure 5 As shown, a method for preparing a high-performance asphalt-based porous carbon material comprises the following steps in sequence: S1. Crushing: crushing the asphalt raw material to 200 mesh to obtain crushed material; S2, heat treatment: heat treating the crushed material under a nitrogen atmosphere until the light component content in the crushed material is 58wt%, to obtain a precursor, wherein the heat treatment temperature is 300°C and the time is 45min; S3, pre-oxidation: in a high-temperature carbonization furnace, the precursor is oxidized to obtain a pre-oxidized material, wherein the oxidation atmosphere is air, the oxidation temperature is 270° C., and the oxidation time is 3.0 h; S4, air flow crushing: performing air flow crushing operation on the pre-oxidized material, crushing it to D50=7μm, and obtaining a granular material; S5, carbonization: in a high-temperature carbonization furnace, the granular material is carbonized to obtain a carbonized product, wherein the carbonization temperature is 600° C., the constant temperature carbonization time is 4 hours, and the heating rate from room temperature to the carbonization temperature is 5° C. / min; S6, activation: the carbonized product is left in a high-temperature carbonization furnace, and an alkaline activator is added to perform an activation operation to obtain an activated product, wherein the alkaline activator is potassium hydroxide, and the weight ratio of potassium hydroxide to the carbonized product is 2:1, the atmosphere of the activation operation is nitrogen, the activation temperature is 850°C, and the activation time is 1.5h; S7, acid washing and water washing: the activated product is subjected to acid washing and water washing operations for multiple times in sequence to obtain a washing material, wherein dilute hydrochloric acid is used for the acid washing operation and distilled water is used for the water washing operation: S8. Drying: performing hot air drying operation on the washed material to obtain a final high-performance asphalt-based porous carbon material, wherein the end point of the hot air drying operation is that the moisture content of the washed material is ≤0.03wt%.
[0046] The high-performance asphalt-based porous carbon material has a hierarchical pore structure, which includes micropores, mesopores and macropores. The pore size of the micropores is less than 2nm, the pore size of the mesopores is 2-50nm, and the pore size of the macropores is >50nm.
[0047] The application of this high-performance asphalt-based porous carbon material: used to prepare negative electrodes for lithium-ion batteries, sodium-ion batteries and supercapacitors.
[0048] Comparative Example 1 The high-performance asphalt-based porous carbon material, preparation method and application thereof in this comparative example are different from those in Example 1 in only one respect: In S2, the heat treatment operation time is relatively short and the temperature is low, and the light component content in the crushed material is 77.5wt%.
[0049] Comparative Example 2 The high-performance asphalt-based porous carbon material, preparation method and application thereof in this comparative example are different from those in Example 1 in only one respect: In S4, the D50 of the granular material is 55.0 μm.
[0050] Comparative Example 3 The high-performance asphalt-based porous carbon material, preparation method and application thereof in this comparative example are different from those in Example 1 in only one respect: Neither the two steps of S6, activation, nor S7, acid washing and water washing are performed, that is, after the carbonized product is taken out of the high-temperature carbonization furnace, hot air drying operation is performed as needed, which is the final high-performance asphalt-based porous carbon material.
[0051] Comparative Example 4 The high-performance asphalt-based porous carbon material, preparation method and application thereof in this comparative example are different from those in Example 1 in only one respect: S7, the acid washing and water washing steps are not performed, that is, the activated product is directly subjected to hot air drying operation, which is the final high-performance asphalt-based porous carbon material.
[0052] Comparative Example 5 The high-performance asphalt-based porous carbon material, preparation method and application thereof in this comparative example are different from those in Example 1 in only one respect: In S8, the drying time is relatively short and the moisture content of the washing material is 0.05-0.06 wt %.
[0053] Parameter measurement In the above 5 embodiments and 5 comparative examples, 10 samples were respectively taken out for parameter measurement, and the average value was finally taken and recorded in the following table. Specific surface area (m² / g) Micropore specific surface area (m² / g) Pore volume (cm³ / g) Micropore volume (cm³ / g) Average pore size (nm) Microporosity (%) Example 1 2586.35 2323.28 1.168 0.941 1.81 80.52 Example 2 2419.67 2032.10 1.063 0.806 1.76 75.80 Example 3 1931.51 1531.57 0.896 0.631 1.85 70.33 Example 4 890.25 747.05 0.422 0.295 1.90 69.79 Example 5 1326.90 1106.50 0.563 0.433 1.69 76.88 Comparative Example 1 1767.85 909.52 0.659 0.350 1.78 53.21 Comparative Example 2 1478.02 1255.29 0.626 0.494 1.69 78.91 Comparative Example 3 459.52 335.23 0.220 0.131 2.52 59.80 Comparative Example 4 850.20 665.24 0.502 0.322 2.22 65.30 Comparative Example 5 1800.85 1296.88 1.108 0.759 1.98 68.52
[0054] Data analysis First, the porous carbon materials in Examples 1, 2, and 3 have relatively large specific surface areas and pore volumes, and the graded pore structures are mostly micropores, which are more conducive to the conductive properties of the corresponding silicon-carbon negative electrodes.
[0055] Second, the parameters of the porous carbon materials in Examples 4 and 5 are obviously inferior to those in Examples 1, 2, and 3. The reason may be that the carbonization temperature is too high and the amount of alkali is too small, which is not conducive to the activation of the material.
[0056] Third, the porous carbon materials in Comparative Examples 1-5 have smaller specific surface areas and smaller pore volumes than those in Examples 1, 2, and 3 to a certain extent, which proves the necessity and importance of the original limited ranges corresponding to the differences between the comparative examples and Example 1. Fourth, among comparative examples 1-5, comparative example 3 has the smallest specific surface area and the smallest pore volume, which verifies the importance of the two steps of activation and acid washing and water washing.
[0057] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various modifications can be made within the knowledge of ordinary technicians in the technical field without departing from the purpose of the present invention. These are all non-creative modifications and are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A method for preparing a high-performance asphalt-based porous carbon material, characterized in that The following steps are included in sequence: S1. Crushing: crushing the asphalt raw material to 200 mesh to obtain crushed material; S2. Heat treatment: heat treating the crushed material under a nitrogen atmosphere until the light component content in the crushed material is 45-72 wt % to obtain a precursor; S3, pre-oxidation: in a high-temperature carbonization furnace, the precursor is oxidized to obtain a pre-oxidized material; S4, air flow crushing: the pre-oxidized material is subjected to air flow crushing operation to crush it to D50=5-8μm to obtain a granular material; S5, carbonization: in a high-temperature carbonization furnace, carbonizing the granular material to obtain a carbonized product; S6, activation: the carbonized product remains in the high-temperature carbonization furnace, and an alkaline activator is added to perform an activation operation to obtain an activated product; S7, acid washing and water washing: the activated product is subjected to several groups of acid washing and water washing operations in sequence to obtain a washing material: S8, drying: performing hot air drying operation on the washed material to obtain the final high-performance asphalt-based porous carbon material.
2. The method for preparing a high-performance pitch-based porous carbon material according to claim 1, characterized in that: In S2, the heat treatment temperature is 150-550°C and the time is 30-300 min.
3. The method for preparing a high-performance pitch-based porous carbon material according to claim 1, characterized in that: In S3, the atmosphere of the oxidation operation is oxygen or air, the oxidation temperature is 150-400°C, and the oxidation time is 2-5h.
4. The method for preparing a high-performance pitch-based porous carbon material according to claim 1, characterized in that: In S5, the temperature of the carbonization operation is 400-1000°C, the constant temperature carbonization time is 2-4h, and the heating rate from room temperature to the carbonization temperature is 2-7°C / min.
5. The method for preparing a high-performance pitch-based porous carbon material according to claim 1, characterized in that: In S6, the alkaline activator is any one of potassium hydroxide and sodium hydroxide or a mixture of the two.
6. The method for preparing a high-performance pitch-based porous carbon material according to claim 1, characterized in that: In S6, the weight ratio of the alkaline activator to the carbonized product is (1-4):1, the atmosphere of the activation operation is nitrogen, the activation temperature is 600-1000°C, and the activation time is 1-2h.
7. The method for preparing a high-performance pitch-based porous carbon material according to claim 1, characterized in that: In S7, dilute hydrochloric acid is used for pickling operation, and the combination of pickling and water washing is repeated ≥ 3 times.
8. The method for preparing a high-performance pitch-based porous carbon material according to claim 1, characterized in that: In S8, the end point of the hot air drying operation is that the moisture content of the washing material is ≤0.03wt%.
9. A high-performance pitch-based porous carbon material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The high-performance asphalt-based porous carbon material has a hierarchical pore structure, which includes micropores, mesopores and macropores. The pore size of the micropores is <2nm, the pore size of the mesopores is 2-50nm, and the pore size of the macropores is >50nm.
10. An application of the high-performance pitch-based porous carbon material as claimed in claim 9, characterized in that: The high-performance asphalt-based porous carbon material is used to prepare negative electrodes of lithium-ion batteries, sodium-ion batteries and supercapacitors.
Citation Information
Patent Citations
Preparation method of coal tar pitch substrate layer porous carbon material
CN114751410A
Preparation method and application of asphalt-based branched porous carbon material
CN117049539A
Asphalt-based porous carbon material as well as preparation method and application thereof
CN117486211A
Asphalt-based activated carbon as well as preparation method and application thereof
CN117623306A
High-performance asphalt-based porous carbon material and preparation method thereof
CN118206115A
Cited By
Preparation method and application of high-performance biomass-based porous carbon material
CN119551676A
High-performance asphalt-based porous carbon as well as preparation method and application thereof
CN121020582A
High performance pitch-based porous carbon, and preparation method and application thereof
CN121020582B
Porous carbon material for pitch-based lithium ion battery silicon-carbon negative electrode and preparation method of porous carbon material
CN121063530A
Method for preparing high-defect coal pitch-based porous carbon through in-situ oxidation-carbonization in air
CN121394187A